The Best Malaysian SMEs Practices in Solid Waste Management: A Case Study - Abu, Noor Hidayah; Lim, Hui Kheng; Mansor, Mohd Fitri (American Scientific Publishers, 2015)
Waste management is on of the most important issues of manufacturing. 70% of wastes are produced by manufacturer everyday. Large scale organizations have received full attention from many researches with respect to waste management practices and Critical Success Factors (CSFs) that contribute to successful waste management. However, small and medium enterprises (SMEs) did not received adequate attention from researcher. This study was preferred with the main objectives to determine the waste management practices especially in SMEs. In this research, a qualitative method based on interview was implemented. Two manufacturing companies was selected to identify in depth about their practices on waste management. The results of the study have indicated that there are two types of best waste practices implemented by SMEs; monitoring waste expenditures and waste auditing. The results presented a clarified view of waste management practices based on SMEs practices